Optimization of Green Methods for Extraction of Polysaccharides from Fruits of Pithecellobium dulce - Preethi, S.; Saral, A. Mary (Asian Journal of Chemistry, 2017)
This study was conducted to develop a rapid, simple microwave assisted extraction method for the quantification of polysaccharide contents from Pithecellobium dulce pods utilizing fundamental principles of Green Chemistry. The plant is reported to be a folk remedy for ear and tooth ache. It also acts as an emollient, anodyne and larvicidal in folk medicine. As the fruit is liked by common people of Vellore city and throughout the country, a scientific investigation on the edible part of the plant was initiated in our laboratory. Optimization of extraction procedures using modern technologies significantly reduces the quantity of solvent consumed and waste generated during an extraction process. The optimal conditions were determined as follows: 50 % microwave power, an irradiation time of 3 min and a solid-liquid ratio of 1:20 g mL-1. Analysis of variance showed that the contribution of the quadratic model was significant for the responses. Under the optimum conditions, the extraction yield of crude polysaccharides was 63.7 %. This paper outlines a systematic approach for optimization of an extraction procedure for isolation of potential polysaccharide. The extracts were tested to determine the total polysaccharide content by phenol sulphuric acid method.